1987
DOI: 10.1164/ajrccm/136.3.710
|View full text |Cite
|
Sign up to set email alerts
|

Metachromatic Cell Progenitors and Specific Growth and Differentiation Factors in Human Nasal Mucosa and Polyps

Abstract: We previously demonstrated that fluctuations in circulating metachromatic cell progenitors were inversely related to nasal metachromatic cell (NMC) counts and nasal symptoms in allergic rhinitis. Now, we have quantitated NMC progenitors and lineage-specific growth factors using a hemopoietic colony assay. Cell suspensions from excised collagenase-treated nasal polyps (n = 7) contained 3.8 +/- 1.1 granulocyte colony-forming cells per 10(6) cells plated, compared to less than or equal to 0.5 in human tonsil susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 16 publications
5
46
0
Order By: Relevance
“…by using rosetting with sheep erythrocytes treated with 2-aminoacetylisothiouronium bromide hydrobromide (Sigma) (33,34 Our previous work suggesting the elaboration of nasal mucosal basophil/mast cell growth-promoting factors in nasal allergy (14)(15)(16)(17)(18) supports the concept that, in situ, growth and differentiation of hemopoietic cells are involved in allergic inflammatory disease. NGF is secreted by fibroblasts (46) and can induce in dose-dependent manner significant increases in mast cell numbers of both mucosal and connective tissue type, according to their normal predominance in a particular tissue, after injection into neonatal rats (8,9).…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…by using rosetting with sheep erythrocytes treated with 2-aminoacetylisothiouronium bromide hydrobromide (Sigma) (33,34 Our previous work suggesting the elaboration of nasal mucosal basophil/mast cell growth-promoting factors in nasal allergy (14)(15)(16)(17)(18) supports the concept that, in situ, growth and differentiation of hemopoietic cells are involved in allergic inflammatory disease. NGF is secreted by fibroblasts (46) and can induce in dose-dependent manner significant increases in mast cell numbers of both mucosal and connective tissue type, according to their normal predominance in a particular tissue, after injection into neonatal rats (8,9).…”
Section: Methodsmentioning
confidence: 78%
“…We have previously shown that basophil/mast cell progenitors, a subpopulation of eosinophil colony-forming cells (12), circulate in normal human subjects (13), are increased in atopic subjects (14), and are found in the nasal mucosa of patients with nasal polyps (15)(16)(17). Basophil/mast cell and eosinophil differentiation-promoting factors are produced by human nasal polyp and allergic rhinitis mucosal epithelial scrapings in vitro, suggesting the importance of locally derived factors in the regulation of numbers of these specialized granulocytes in allergic inflammation (17,18).…”
mentioning
confidence: 99%
“…HT-29 cells were cultured in McCoy's 5A (Gibco) medium supplemented with 10 % heat-inactivated foetal bovine serum (FBS; Gibco) and 100 U/ml streptomycin and penicillin (Gibco) with pH of 7.2 and osmolality of 290 mOsm/kg (Otsuka et al 1987). Cultures were maintained at 37°C in 5 % CO 2 in air within a humidified incubator, with media replenished every 1-2 days.…”
Section: Cell Line and Culture Conditionsmentioning
confidence: 99%
“…Here, detached nasal cells can be harvested after rinsing both nostrils with physiological saline. On the other hand, the scraping method can be performed with a sharp curette without anesthesia and achieve accurate sampling location, repeated sampling work, stripping out only epithelium and gaining sufficient amount of cells Alford et al, 1969;Otsuka et al, 1987;Zhou et al, 2009). In the case of the brushing techniques, cells can be obtained by rotating a small nylon brush in the epithelium and soaking procedure .…”
Section: Sampling Technique For Nasal Cells From Tissuementioning
confidence: 99%
“…Nasal lavage , Scraping Agu et al (2009), Alford et al (1969), Otsuka et al (1987), , Dissection Coste et al (1996) This table is a modified and supplemented version of previous reports (Schmidt et al, 1998 …”
mentioning
confidence: 99%